Penerapan Buku Saku “Peduli Stunting” Terhadap Tingkat Pengetahuan dan Sikap Ibu di Wilayah Pinggiran Sungai Kapuas Kota Pontianak - Masmuri, Masmuri; Seprian, Dwin; Limansyah, Dodik; Rusnaini, Rusnaini (Universitas Malahayati, 2024)
ABSTRACT Stunting is one of the problems that exists in communities along the Kapuas River in West Kalimantan. Low levels of knowledge and inadequate attitudes or practices regarding the care of children with stunting are some of the causes of stunting. The characteristics of the people on the banks of the Kapuas River are generally people who are still very closely related to the culture they adhere to. This research aims to examine the effectiveness of implementing the